Patient-reported outcomes of joint-preserving surgery for moderate hallux rigidus: a 1-year follow-up of 296 patients from Swefoot - Cöster, Marcus E; Montgomery, Fredrik; Cöster, Maria C (Acta Orthopaedica, 2020)
Background and purpose — Hallux rigidus (HR) may cause decreased range of motion, joint pain, and gait disturbances. There is a lack of evidence regarding the outcome of different surgical procedures for moderate HR. We report patient-reported outcomes after joint-preserving surgical procedures for moderate HR. Patients and methods — We included 296 patients registered in Swefoot (Swedish national registry of foot and ankle surgery) who underwent primary surgery for moderate HR 2014 through 2018. We extracted information on anthropometrics, grading of HR, chosen surgical procedure, and patient-reported data including the PROMs SEFAS (summary score 0–48) and EQ-5D-3L (index 0–1) preoperatively and 1 year postoperatively. Results — 115 patients underwent metatarsal decompression (i.e., Youngswick) osteotomy (YOT) and 181 underwent cheilectomy. The mean improvement in SEFAS score 1 year after surgery was 12 points (95% CI 10−13) for YOT and 10 points (CI 9−12) for cheilectomy. Also, EQ-5D improved in both groups. Patients who underwent YOT were more satisfied with the procedure (84% vs. 70 % for cheilectomy, p = 0.02). Interpretation — Surgically treated patients with moderate HR improved after both YOT and cheilectomy, according to patient-reported data from Swefoot. Patients who underwent a YOT were more satisfied with their procedure. One possible explanation may be that more patients in the YOT group had a concomitant hallux valgus; however, we have no information on this.